2016
DOI: 10.1111/sed.12321
|View full text |Cite
|
Sign up to set email alerts
|

Early Jurassic North Atlantic sea‐surface temperatures from TEX86 palaeothermometry

Abstract: Early Jurassic marine palaeotemperatures have been typically quantified by oxygen-isotope palaeothermometry of benthic and nektonic carbonate and phosphatic macrofossils. However, records of Early Jurassic sea-surface temperatures that can be directly compared with general circulation model simulations of past climates are currently unavailable. The TEX 86 sea-surface temperature proxy is based upon the relative abundance of glycerol dialkyl glycerol tetraethers preserved in organic-carbon-bearing sediments. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 63 publications
2
16
0
Order By: Relevance
“…IsoGDGTs derived from the aquatic archaea can be used as temperature proxies via the TEX 86 index (Schouten et al, ). An increasing number of studies have found that in situ production of isoGDGTs within the marine sediments can affect TEX 86 values and confound temperature estimates (Lincoln et al, ; Robinson et al, ; Zhang, Pagani, et al, ; Zell et al, ). A recent investigation of two marine ammonia‐oxidizing Thaumarchaeota cultures demonstrated the relative increase in isoGDGT‐2 under low O 2 concentrations (Qin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…IsoGDGTs derived from the aquatic archaea can be used as temperature proxies via the TEX 86 index (Schouten et al, ). An increasing number of studies have found that in situ production of isoGDGTs within the marine sediments can affect TEX 86 values and confound temperature estimates (Lincoln et al, ; Robinson et al, ; Zhang, Pagani, et al, ; Zell et al, ). A recent investigation of two marine ammonia‐oxidizing Thaumarchaeota cultures demonstrated the relative increase in isoGDGT‐2 under low O 2 concentrations (Qin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Organic temperature proxies (U K ′ 37 , TEX 86 , LDI) 3 5 have proved to be indispensable in this context. These tools are frequently employed in marine sediment sequences to reconstruct past sea surface temperatures and have been used to establish high-resolution palaeotemperature records from all parts of the oceans 5 7 and in sediments dating back to the Early Jurassic (~200 Ma) 8 . As such, organic temperature proxies have significantly broadened our knowledge on Earth’s long-term climate evolution over geological timescales 9 , 10 as well as during abrupt climate change events 11 .…”
Section: Introductionmentioning
confidence: 99%
“…During the past three decades, several proxies based on lipid biomarkers have been proposed for reconstructing SST, inter alia: the proxy based on long-chain alkenones (C 37 , C 38 and C 39 ) (Brassell et al, 1986; U K ′ 37 Conte et al, 2006;Rosell-Melé and Prahl, 2013;Tierney and Tingley, 2018), TEX 86 (TetraEther indeX of tetraethers consisting of 86 carbon atoms) based on isoprenoid glycerol dialkyl glycerol tetraethers (isoGDGTs) (Schouten et al, 2002;Kim et al, 2008Kim et al, , 2010, and the Long chain Diol Index (LDI) based on long chain diols compounds (Rampen et al, 2012). These existing palaeothermometers have been widely applied to reconstruct SSTs at various spatial and temporal scales through the Holocene (Moossen et al, 2015), Quaternary (Naafs et al, 2012;Lopes dos Santos et al, 2013) and deeper time in the Cenozoic and Mesozoic (Herbert and Schuffert, 1998;Bijl et al, 2013;Inglis et al, 2015;Herbert et al, 2016;Robinson et al, 2017;de Bar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%